Fluoroelastomers handbook : the definitive user's guide - Drobny, Jiri George (William Andrew is an imprint of Elsevier, 2016)
Fluoroelastomers Handbook: The Definitive User's Guide, Second Edition is a comprehensive reference on fluoroelastomer chemistry, processing technology, and applications. It is a must-have reference for materials scientists and engineers in the automotive, aerospace, chemical, chemical process, and power generation industries. Covering both physical and mechanical properties of fluoroelastomers, it is useful in addressing daily challenges in the use of these materials, as well as the challenges posed in long-term research and development programs. Since the publication of the previous edition in 2005, many new findings and developments in chemistry, technology, and applications of fluoroelastomers have taken place. This is the only book with updated information on the manufacturing process, cross-linking chemistry and the formulation of compounds, as well as mixing, processing, and curing methods. A fully revised chapter is included on applications and examples of fluoroelastomer compounds. Safety, hygiene, and disposal standards and guidelines have been updated, and a new chapter has been added to discuss new developments and current trends, helping engineers and materials scientists stay ahead of the curve.
Keywords: Elastomers -- Handbooks, manuals, etc.; Fluorocarbons -- Handbooks, manuals, etc.; elektronické knihy; electronic books